ASSESSING CULTURAL CONTENT IN ENGLISH TEXTBOOK FOR HIGH SCHOOL GRADE 12 STUDENTS: A CASE STUDY - Ardnyananisari, Fannysa Dyah; Ratri, Devinta Puspita (English Review: Journal of English Education, 2024)
This research analyzes the cultural content presentation in the textbook "Bahasa Inggris" for the twelfth-grade high school by the Ministry of Education and Culture of the Republic of Indonesia, where this book is part of the 2013 curriculum. The analysis of cultural content in this research uses the three-source analysis theory of cultural information by Cortazzi and Jin, which will then be combined with Byram's, theory by providing codes in eight categories. Cortazzi and Jin's theory describes categorization in the presentation of cultural content in English textbooks. Meanwhile, Byram's checklist is used to classify cultural content, which has been categorized into these eight categories. This checklist reveals cultural information and how the content meets language and culture learning and teaching needs. The findings show that this EFL textbook presents source culture and target culture content, but international culture is not present. Material about source culture is presented most in this textbook.